Ensuring non-repudiation in human conversations over VoIP communications. (2016) - Cattaneo, Giuseppe; Catuogno, Luigi; Petagna, Fabio; Roscigno, Gianluca
Nowadays, plenty of sensitive transactions such as home banking and goods and services purchase are provided through call centres. This scenario raises two major issues: 1) both peers should be ensured of each other's identity; 2) each peer should be guaranteed that the other could not cheat about the communication contents. Off-the-shelf solutions addressing communication reliability are mainly based on proprietary technologies which often suffer from scarce interoperability. This paper addresses the achievement of strong peers authentication and non-repudiation of human conversations over VoIP communications. Our solution achieves low costs and high interoperability as it is built on top of open and standard technologies. As proof of concept, prototype implementation is presented and discussed.